GIS/GIS identification of potential bus stop locations and passenger's access and egress points - Bachok, Syahriah; Ponrohono, Zakiah; Mohamed Osman, Mariana; Bohari, Zulfadly Azizi (2013)
This research reports the study of identification and d etermination of bus stop locations and passengers boarding and alighting positions through the application of G lobal P ositioning S ystem (GPS) and Geographical I nformati on S ystem (GIS) method s . Previously, the location s of bus stop were designed without much consideration to the access and egress points of prospective passengers and other users. Using the case study of public bus operation in Kerian , Perak , a district in Malaysia , GPS method captured the locational points during on - board survey s while the GIS method produced the points mapping . As a result, the possible bus stop locations can be recorded and validated based on the passengers access and egrees points and vo lume pattern s . This research aims to analyse these empirical data to estimate the possible location of new bus stops within certain distance ratio s . From this findings, public bus operators and authorities can determine/allocate/distribute the bus stop loc ations that may reduce the waiting time .